Managing Public Organizations : Lessons From Contemporary European Experience (SAGE Publications, 1993)
Managing Public Organizations presents the case for the development of public management and indicates the directions it should take. It reviews the progress of new management initiatives in the European public sphere; examines the role of the public manager and the organization of public bodies; and considers the potential for change. The contributors reject the notion that there are formulas for management innovation or that general rules from private sector management can be applied. They emphasize the need to develop a concept of management that is appropriate for public organizations.